2000
DOI: 10.1038/sj.bmt.1702433
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation following busulfan, etoposide and cyclophosphamide in patients with non-Hodgkin's lymphoma

Abstract: Summary:The purpose of the study was to determine the toxicities and effectiveness of a novel preparative regimen of busulfan (Bu) 14 mg/kg, etoposide 50 or 60 mg/kg, and cyclophosphamide (Cy) 120 mg/kg in non-Hodgkin's lymphoma (NHL) and to analyze results using doses based on different body weight parameters and the two different etoposide doses. Three hundred and eightytwo patients aged 16 to 72 underwent first autologous transplantation with mobilized peripheral blood progenitor cells between August 1992 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 43 publications
9
44
0
Order By: Relevance
“…[15][16][17] However, these studies varied from ours in terms of dose and dosing weight adjustments used. Weight adjustments can have an impact on the actual amount of drug administered to patients, potentially impacting transplant outcomes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[15][16][17] However, these studies varied from ours in terms of dose and dosing weight adjustments used. Weight adjustments can have an impact on the actual amount of drug administered to patients, potentially impacting transplant outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…In another study of 382 NHL patients, the median time to ANC and platelet recovery was 9 and 16 days, respectively. 16 In this study, doses of oral BU, etoposide and CY were identical to those in our conditioning regimen; however, all chemotherapy was dosed using a different dosing weight algorithm: chemotherapy was dosed on the lesser of ideal or actual body weight unless the patient's actual body weight was 20% greater than their ideal body weight, in which case an adjusted body weight was used. A study of 65 NHL patients reported similar results to ours, with a median time to ANC and platelet recovery at 9 and 11 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of etoposide has not been demonstrated to offer an advantage when added to Bu/cyclophosphamide in patients with leukemias in a prospective study. Studies in adults with leukemias and lymphomas have noted an increase in hepatotoxicity, including veno-occlusive disease (VOD), dermatologic toxicity, and mucositis, [22][23][24][25] without an increase in treatment-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The details of administration and supportive care have been previously described. 15 G-CSF was administered to all patients to accelerate neutrophil recovery beginning on either the day following stem cell infusion or 5 days following infusion. 16 Follow-up Following auto-HCT, patients were followed either at the Cleveland Clinic or at their local oncologist's office.…”
Section: Preparative Regimensmentioning
confidence: 99%